EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK KONTRAK PERILAKU UNTUK MENGURANGI PERILAKU BOLOS PADA SISWA KELAS XI MAN 1LEBAK - Siti Cela Hadijah; Alfiandy Warih Handoyo; Evi Afiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the phenomenon of student truancy—specifically unauthorized absences, leaving class during lessons, and missing learning activities without a valid reason. Such behavior can negatively impact students' academic achievement, discipline, sense of responsibility, and social development. The study aimed to determine the effectiveness of group counseling using the behavior contracting technique in reducing truancy among Grade XI students at MAN 1 Lebak during the 2025/2026 academic year. A quantitative approach was employed using the Single-Subject Research (SSR) method with an A-B-A design, comprising an initial baseline phase (A1), an intervention phase (B), and a second baseline phase (A2). Seven students participated in the study, selected via purposive sampling based on questionnaire results indicating high levels of truancy. Data analysis involved visual analysis—both within and across conditions—supported by N-Gain calculations. The results showed overlap values of 29% for subjects FI, H, and YY, and 0% for subjects KJES, HR, RAF, and MR during the A1-B transition. In the B-A2 transition, all subjects exhibited an overlap value of 0%, indicating consistent behavioral change following the intervention. Furthermore, all subjects showed improved behavioral scores—signifying a reduction in truancy—evidenced by fewer unauthorized absences, a decrease in the habit of leaving class during lessons, and increased discipline and adherence to school regulations. Thus, group counseling utilizing the behavior contracting technique is effective in reducing truancy among Grade XI students at MAN 1 Lebak.